2022
DOI: 10.1017/s0143814x21000143
|View full text |Cite
|
Sign up to set email alerts
|

Punctuated equilibrium and progressive friction in socialist autocracy, democracy and hybrid regimes

Abstract: The analysis of public policy agendas in comparative politics has been somewhat limited in terms of geography, time frame and political system, with studies on full-blown autocracies and hybrid regimes few and far between. This article addresses this gap by comparing policy dynamics in three Hungarian regimes over 73 years. Besides our theoretical contribution related to policy-making in Socialist autocracy and illiberal democracy, we also test hypotheses related to non-democratic regimes. We find that – simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on the budget data from the United States, the United Kingdom, Germany, and France, Jones and others (2009) concluded that punctuated equilibrium can be considered as a rule of thumb for a public budget. Budget data from authoritative regimes (including Brazil, Hungary, Turkey, Malta, and Russia) followed PET even before they transformed into democratic institutions (Baumgartner et al, 2017; Rey, 2014; Sebők et al, 2022).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the budget data from the United States, the United Kingdom, Germany, and France, Jones and others (2009) concluded that punctuated equilibrium can be considered as a rule of thumb for a public budget. Budget data from authoritative regimes (including Brazil, Hungary, Turkey, Malta, and Russia) followed PET even before they transformed into democratic institutions (Baumgartner et al, 2017; Rey, 2014; Sebők et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Some scholars conducted broader comparative studies that focus on different political systems. Sebők and others (2022) compared socialistic authorities, democratic institutions, and hybrid regimes and found that PET is applicable even beyond democracy. Based on the political spectrum, from the least democratic to the most democratic institutions, Jones and others (2019) extracted from previous literature four key factors that may affect punctuations in policy making: friction, incentives to solve problems, centralization, and information.…”
Section: Literature Review and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation